Dietary habits among health professionals working in a district hospital in KwaZulu-Natal, South Africa - Kunene, Siyabonga H. (Afr J Prim Health Care Fam Med, 2017)
INTRODUCTION: The burden of diseases associated with unhealthy lifestyle behaviours continues to increase in the low- and middle-income countries including South Africa. Among the affected population are the health professionals who are assumed to be knowledgeable about healthy eating. AIM: This study aimed to determine the dietary habits of health professionals in a public district hospital in KwaZulu-Natal, South Africa. METHODS: A cross-sectional survey was conducted in 2012 among 109 randomly selected health professionals. Each received a questionnaire consisting of mostly closed and few open-ended questions. Its main focus was the dietary and eating habits of the professionals. An ethical clearance was granted by the Medunsa Research and Ethics committee at the University of Limpopo. Permission to conduct the study was sought and obtained from participants as well. Descriptive statistics and frequencies were used to analyse data. RESULTS: A 100% (109) response rate was achieved. The majority skipped meals especially breakfast with a significant positive correlation between breakfast intake per week and age (r = 0.98, p = 0.048). The majority consumed a lot of unhealthy foods and carbonated beverages with sugar. Consumption of fruits, vegetables, high fibre and whole grain foods was less common. CONCLUSION: The study showed poor eating habits among participants. Urgent health interventions are therefore indicated to highlight the importance of healthy eating habits among the entire population.